Big kibble : the hidden dangers of the pet food industry and how to do better by our dogs - Buckley, Shawn Richard, 1964-; Chavez, Oscar; Paris, Wendy (Journalist) (St. Martin's Press, 2020)
"A big, inside look at the shocking lack of regulation within the pet food industry, and how readers can dramatically improve the quality of their dogs' lives through diet. What's really going into commercial dog food? The answer is horrifying. Big Kibble is big business: $75 billion globally. A handful of multi-national corporations dominate the industry and together own as many as 80% of all brands. This comes as a surprise to most people, but what's even more shocking is how lax the regulations and guidelines are around these products. The guidelines-or lack thereof-for pet food allow producers to include ever-cheaper ingredients, and create ever-larger earnings. For example, "legal" ingredients in kibble include poultry feces, saw dust, expired food, and diseased meat, among other horrors. Many vets still don't know that kibble is not the best food for dogs because Big Kibble funds the nutrition research. So far, these corporations have been able to cut corners and still market and promote feed-grade food as if it were healthful and beneficial-until now. Just as you are what you eat, so is your dog. Once you stop feeding your dog the junk that's in kibble or cans, you have taken the first steps to improving your dog's health, behavior and happiness. You know the unsavory side of Big Tobacco and Big Pharma. Now get ready to learn about unsavory Big Kibble, and a brighter path forward for you and your pet"--